The Bedtime Book - Marendaz, S.; Gledhill, Carly (Wilton, CT : Tiger Tales, 2020)
Join Mouse and Frank, the dog, as they look for Mouses favorite bedtime book. Its nighttime but Mouse is not asleep. Mouse cannot find her bedtime book! Where could it be? And how can she possibly sleep without it?
3-6
P-1
Keywords: Friendship -- Juvenile fiction; Animals -- Juvenile fiction; Books and reading -- Juvenile fiction; Friendship -- Fiction; Animals -- Fiction; Books and reading -- Fiction